MODIFIED ELLIPTICAL COORDINATE SYSTEM FOR PROBLEMS OF MATHEMATICAL PHYSICS WITH ELLIPTICAL SYMMETRY CYLINDER - Popov, M.; Zavislyak, I. V.; Golovach, G. P. (Radio Electronics, Computer Science, Control, 2024)
The original modified elliptical coordinate system is submitted, its properties are considered, useful relationships are given. It was suggested to use this coordinate system for mathematical physics problems with the symmetry of the elliptical cylinder, in particular for eigenwaves and eigen oscillations problems in waveguides and of elliptic cross-section resonators, the examples of application were demonstrated.